The Effect Of Group Guidance With Self Affirmation Technique On Improving Self Awareness Of Students At Sma It Al Fityah Pekanbar - Reza Maha Sari Sopiyah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Students still lack a clear understanding of themselves, their emotions, and their responsibilities. This can impact their self-confidence and behavior at school. Therefore, self-affirmation techniques are important for improving student self-awareness. This study aimed to examine the effect of group guidance services using self-affirmation techniques on improving self-awareness in eleventh-grade students at SMA IT Al Fityah Pekanbaru. This study used a quantitative approach with a one-group pretest-posttest design. Ten students were selected through purposive sampling based on low and medium self-awareness categories. Data were collected using a self-awareness scale consisting of 28 valid items with a Likert scale. The research instrument had high reliability with a Cronbach's Alpha value of 0.916. Data were analyzed using descriptive statistics, the Wilcoxon test, and the normalized N-Gain test. The results showed that before the intervention, 20% of students were in the low category and 80% in the medium category. After eight treatment sessions, 80% of students were in the medium category with substantial score improvements, and 20% reached the high category. The Wilcoxon test results showed a significant difference between pretest and posttest scores with a p-value of 0.005. The average N-Gain score of 0.32 indicated moderate effectiveness. These findings suggest that group guidance services using self-affirmation techniques can improve student self-awareness and can be used as an alternative guidance and counseling intervention in high schools.